2012
DOI: 10.1128/jvi.06194-11
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolin Interacts with US11 Protein of Herpes Simplex Virus 1 and Is Involved in Its Trafficking

Abstract: Herpes simplex virus type 1 (HSV-1) infection induces profound nucleolar modifications at the functional and organizational levels, including nucleolar invasion by several viral proteins. One of these proteins is US11, which exhibits several different functions and displays both cytoplasmic localization and clear nucleolar localization very similar to that of the major multifunctional nucleolar protein nucleolin. To determine whether US11 interacts with nucleolin, we purified US11 protein partners by coimmunop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 40 publications
1
42
1
Order By: Relevance
“…Us11 shuttles between the nucleus and the cytoplasm (43), and infection by two herpesviruses, HCMV and murine cytomegalovirus, causes the sequestration of PKR in the nucleus (44,45). We observed that a similar relocalization occurs in HSV-1-infected cells and that this depends on Us11 expression (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…Us11 shuttles between the nucleus and the cytoplasm (43), and infection by two herpesviruses, HCMV and murine cytomegalovirus, causes the sequestration of PKR in the nucleus (44,45). We observed that a similar relocalization occurs in HSV-1-infected cells and that this depends on Us11 expression (data not shown).…”
Section: Discussionmentioning
confidence: 71%
“…2A). Instead, this initial redistribution was most likely a consequence of the viral disruption of cellular nucleoli (32,33). At 6 hpi, we observed two distinct populations of 7134-infected cells: (i) cells with small replication compartments and diffuse IFI16 staining (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…It is tempting to speculate that NCL could play a similar role in the assembly of the viral nucleocapsid complex. Indeed, NCL has been shown to enhance the release and infectivity of HIV-1 and to be involved in trafficking and nuclear egress of herpesvirus nucleocapsids (49)(50)(51). NCL could act as a chaperone for DENV C, assisting in the assembly of stable nucleoprotein complexes and perhaps aiding in the transport of the nucleocapsid to sites of maturation and egress.…”
Section: Discussionmentioning
confidence: 99%
“…NCL colocalizes with hepatitis D virus delta antigen and interacts with herpes simplex virus 1 protein US11, cytomegalovirus UL44, white-spot syndrome virus VP15, influenza virus (H3N2) NS1, and the NS5B protein of hepatitis C virus. These interactions have been shown to mediate a number of different processes, including protein synthesis, RNA replication, release of virions, and trafficking of viral proteins (48)(49)(50)(51)(52)(53)(54). In addition, NCL has been shown to interact with the untranslated regions (UTR) of several other viruses, including tombusvirus, feline calicivirus, Norwalk virus, and poliovirus, where it may play roles in virus replication (55)(56)(57).…”
mentioning
confidence: 99%